Quantitative evaluation of digital rural public sports service policies based on the PMC index model - Hong Tan; Shijia Liu; Kunyu Li (Frontiers in Public Health)
With the continued advancement of China’s rural revitalization strategy, the high-quality development of rural public sports services has become a key priority in promoting farmers’ health and enhancing social cohesion. The rapid expansion of digital technologies offers new opportunities to overcome longstanding challenges in rural public sports provision. However, the effectiveness of current policy implementation remains uneven and faces multiple constraints. This study applies the Policy Modeling Consistency (PMC) index model to quantitatively evaluate nine representative policies, scoring and analyzing each individually. The findings reveal that only one policy is rated as excellent, five as good, and three as acceptable, with an overall average PMC score of 5.646. These results indicate that while current policies have begun to direct public sports resources toward rural areas, deficiencies remain in terms of implementation strength, coverage scope, and long-term sustainability. Based on these insights, the study recommends enhancing policy incentive mechanisms, improving the adaptability of policy tools, and establishing a cross-sectoral coordination framework to support more integrated and equitable development of urban–rural public sports services.